Respuesta :

Space

Answer:

g(h(n)) = 4n² + 12n

General Formulas and Concepts:

Pre-Algebra

Order of Operations: BPEMDAS

  1. Brackets
  2. Parenthesis
  3. Exponents
  4. Multiplication
  5. Division
  6. Addition
  7. Subtraction
  • Left to Right

Distributive Property

Algebra I

  • Terms/Coefficients
  • Function Notation

Algebra II

  • Composite Functions

Step-by-step explanation:

Step 1: Define

g(n) = 4n

h(n) = n² + 3n

g(h(n)) is n = h(n)

Step 2: Find

  1. Substitute in function h(n) as n:                                                                       g(h(n)) = 4(n²+ 3n)
  2. [Distributive Property] Distribute 4:                                                               g(h(n)) = 4n² + 12n